Autorytety naukowe na miarę czasu - Drozdowicz, Zbigniew (Polska Akademia Nauk, 2018)
In these remarks I make an attempt to understand and present the functioning of authorities in science. I do use in the first place the earlier claims which present this issue in a historical perspective. This allows to grasp the social proces of emergence of the authorities as well the changing of their position in the way they are functioning. Especially the thoughts of Max Weber are being considered by my as useful in this matter. I do share his general thesis saying that even the greatest of scientific authorities – called by me in these remarks ”centennial” – couldn't occur and function without their social and cultural ”background”. This had led in large extent to the situation where these authorities fist played a significant role in the development of science and then went over to a more or less dignified ”retirement”. In this and other issues I present some of my own remarks and sugestions.
Keywords: scientific authorities; creation opf authorities; questioning of authorities; historical and modern conditioning of so called major authorities